Concentration dependent toxicity of microplastics to marine microalgae - Tan Hongmei; Liu Zhoumiao; Liu Yuting; Wu Mengzhen (E3S Web of Conferences)
The widespread distribution of microplastics (MPs) in the environment poses a potential threat to ecosystems. Microalgae are key primary producers in marine ecosystems, and the algae is more sensitive to changes in the ecological environment. Therefore, assessing the toxicity of MPs pollution to microalgae is critically important. In this study, polystyrene (PS) MPs (1 μm) was selected to carry out exposure experiments on Chlorella sp. with the treatment concentrations of 10 and 50 mg/L. At each time period of the PS MPs treatment group, the 50 mg/L exposure level inhibited the growth of Chlorella sp., which was higher than that of 10 mg/L. Experimental data demonstrated the toxicity of PS MPs on Chlorella sp. was concentration-dependent. The maximum growth inhibition rate of PS MPs on Chlorella sp. reached 14% (10 mg/L) and 34.3% (50 mg/L). This research is of great significance for assessing the ecotoxicity of MPs in aquatic ecosystems.